Formulating Strategic Directions for Indigenous Knowledge Management Systems - Tariq, Zaman; Narayanan, Kulathuramaiyer; Wee, Alvin Yeo (2010)
In modern organisational structures knowledge management practices consist of knowledge generation, capture, sharing and application. The organisations emphasize on codification and documentation of implicit knowledge and transform it to explicit form. Indigenous communities however have much less codified knowledge relying mainly on oral and tacit form. The communities have their own processes of storage, leveraging, sharing and applying knowledge which is different from knowledge management processes of corporations and research organizations due to the oral and tacit structures of these processes. In this paper we present a model for formulating strategic directions for an indigenous knowledge management system. We have designed a knowledge management assessment tool for Indigenous Knowledge Management Systems (IKMS) which has been tested in remote community in Bario, Sarawak. On the bases of our assessment of IKMS, community capacity and resources, we have developed a strategic map for IKMS in Bario. This work serves as an extension to the previous literature on designing the Balanced Scorecard for IKMS.